Carers' needs assessment for patients with dementia in Ghana - Nana K. Ayisi-Boateng; Douglas A. Opoku; Phyllis Tawiah; Ruth Owusu-Antwi; Emmanuel Konadu; Georgina T. Apenteng; Akye Essuman; Charles Mock; Bernard Barnie; Peter Donkor; Fred S. Sarfo (AOSIS, 2022)
Abstract Background: Carers of people with dementia (PWD) face a myriad of challenges. As dementia prevalence surges in the sub-Saharan population, the provision of data on the met and unmet needs of caregivers has become paramount. Aim: This study aimed to identify the needs of carers of older adults living with dementia in Ghana. Setting: This study was conducted in Kumasi, Ghana, among participants ≥ 18 years old, serving as carers for PWD. Methods: This was a multicentre cross-sectional study involving carers of patients (≥ 50 years) with dementia. The authors administered the Carer's Needs Assessment for Dementia (CNA-D) questionnaire, containing 18 problem areas with interventions for each problem area. Pearson's correlation analysis was performed to establish a relationship between demographic characteristics, problem areas and intervention score. Results: Fifty participants were recruited with a mean age of 48.8 (± 16.9) years, 72.0% were female participants and 98.0% were family members of PWD. The problem area most frequently identified as no/mild problem was 'legal issues' (92.0%, n = 46), and 'lack of information about dementia' was assessed as severe (48.0%, n = 24). The commonest unmet need was 'printed information material' (84.0%, n = 42), and the commonest met need was 'diagnosis and treatment of carer by a general practitioner' (42.0%, n = 21). There was a statistically negative correlation between age of carer and number of unmet needs (r = −0.308, p = 0.011) and a positive correlation between problem area score and number of unmet needs (r = 0.308, p = 0.030). Conclusion: Effective public education and provision of information on dementia to carers are essential interventions needed to equip them in performing their roles. Contribution: Carers in this study revealed that they lacked information on dementia but their commonest met need was accessibility to their general practitioner. This highlights the importance of promoting knowledge and awareness of dementia among primary care practitioners.